2017
DOI: 10.3892/mmr.2017.6349
|View full text |Cite
|
Sign up to set email alerts
|

miR-217 inhibits osteogenic differentiation of rat bone marrow-derived mesenchymal stem cells by binding to Runx2

Abstract: Abstract. The elucidation of the underlying molecular mechanisms regulating the osteogenic differentiation of bone marrow-derived mesenchymal stem cells (BMSCs) is of great importance in improving the treatment of bone-associated diseases. MicroRNAs (miRNAs) have been proven to regulate the osteogenic differentiation of BMSCs. The present study investigated the role of miR-217 in the osteogenic differentiation of rat BMSCs. It was observed that miR-217 expression levels were downregulated during the process of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Similarly, the expression levels of miR10a/b were observed to be promoted by transforming growth factor β and may increase migration of human glioma cells by targeting phosphatase and tensin homolog (38). Furthermore, a previous study observed that miR-217 may inhibit osteogenic differentiation by regulating runt related transcription factor 2 (39), and miR-217 may inhibit the invasion and proliferation of gastric cancer and osteosarcoma cells (40,41). In the present study, the DEmiRs exhibiting the highest number of associations in the miRNA-mRNA network were miR-6328, miR-653-3p, miR-6321 and miR-3547.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the expression levels of miR10a/b were observed to be promoted by transforming growth factor β and may increase migration of human glioma cells by targeting phosphatase and tensin homolog (38). Furthermore, a previous study observed that miR-217 may inhibit osteogenic differentiation by regulating runt related transcription factor 2 (39), and miR-217 may inhibit the invasion and proliferation of gastric cancer and osteosarcoma cells (40,41). In the present study, the DEmiRs exhibiting the highest number of associations in the miRNA-mRNA network were miR-6328, miR-653-3p, miR-6321 and miR-3547.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study revealed that HMGB1 upregulated the expression levels of p-GSK-3β and β-catenin; blocking the PI3K/AKT/GSK-3 signaling pathway decreased the cell apoptosis rate and the expression levels of MMPs and AdAMTs, indicating that HMGB1 may induce the occurrence and development of KOA by activating the GSK-3β/β-catenin pathway. EST-1 and Runx2 are osteogenic differentiation-specific transcription factors that regulate the transcription of multiple genes (45,46) that play important roles in the formation and differentiation of osteoblasts, differentiation and maturation of chondrocytes, formation and absorption of osteoclasts and production of bone matrix proteins (47,48). In addition, in rheumatoid arthritis, a number of other signaling pathways that may regulate MMPs have also been identified, such as Nrf2/HO-1 signaling (49), NF-κB inflammatory signaling (50,51), mitochondrial/caspase-mediated pathways (52) or mitogen-activated protein kinase signaling pathway (53); however, its role in HMGB1-induced chondrocyte apoptosis requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that a plenty of miRNAs were involved in suppressing osteogenesis by targeting RUNX2, such as miR-103a, 34 miR-133a, 35 miR-135a, 33 miR-204/211, 36 and miR-217. 37 miR-93-3p was reported to be upregulated in HIV-associated neurocognitive-disordered patients, 38 while downregulated in radioresistant nasopharyngeal carcinoma cells. 39 Meanwhile, miR-93-3p was suggested to be a potential biomarker of acute kidney injury (AKI) in intensive care units (ICU), and cardiac surgery (CS) patients since it was significantly downregulated during the days prior to AKI diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Results found that miR‐93‐3p can directly bind to 2310–2316 nt of RUNX2 3′ UTR, which suggested that miR‐93‐3p may regulate RUNX2 expression. Previous studies revealed that a plenty of miRNAs were involved in suppressing osteogenesis by targeting RUNX2, such as miR‐103a, miR‐133a, miR‐135a, miR‐204/211, and miR‐217 . miR‐93‐3p was reported to be upregulated in HIV‐associated neurocognitive‐disordered patients, while downregulated in radioresistant nasopharyngeal carcinoma cells .…”
Section: Discussionmentioning
confidence: 99%